Investigating the Use of C/SiC Ceramic Composites in an Innovative Light-Water Reactor Core Grouping Catcher - Han, Xu; Zhang, Litong; Xing, Ji; Ma, Weimin; Yuan, Yidan; Wang, Haoxuan; Wang, Yiguang; Zeng, Xiao (Frontiers in Energy Research, 2022)
China Nuclear Power Engineering, Northwestern Polytechnical University, and Beijing Institute of Technology have undertaken a joint research work with the goal of developing corium retention containers for use in an innovative light-water reactor core grouping catcher (CGC). In Serious Accidents (SAs), the corium will be retained in the C/SiC ceramic composite spherical shell container and thrown into the pool for passive cooling. In order to investigate the capability of the C/SiC ceramic composites to withstand the high temperature of 1800°C and the huge thermal shock at the initial stage of cooling, in this work, the high-temperature performance of these composites is studied. Furthermore, the compatibility of these composites with corium is investigated, and a retention container design prototype is proposed. The thermal conductivity, thermal expansion coefficient, high-temperature tensile strength, and thermal shock resistance of the candidate C/SiC specimens to be used in the manufacturing of the detention container are measured. The FactSage software package is used for the chemical compatibility study and product composition analysis of the composite SiC deposition layer and corium. The corrosion process of the SiC deposition layer of the composite material caused by corium is investigated through high-temperature corrosion tests and the electron microscopy analysis of the SiC specimen with the incorporation of CeO2. The results show that the C/SiC ceramic composite can meet the design criteria of the CGC corium retention container, and it is impossible to cause a carbon reaction disaster through the failure of the composite SiC deposition layer.